2020
DOI: 10.1017/s0007114519003386
|View full text |Cite|
|
Sign up to set email alerts
|

Micronutrient-fortified infant cereal improves Hb status and reduces iron-deficiency anaemia in Indian infants: an effectiveness study

Abstract: Anaemia affects approximately 69 % of Indian children aged 6–12 months, with Fe deficiency (ID) being a common cause. The effectiveness of micronutrient-fortified infant cereal in improving Fe status and neurodevelopment was evaluated in non-anaemic and mildly anaemic Indian infants. An intervention group (IC) enrolled at age 6 months consumed 50 g/d of rice-based cereal providing 3·75 mg Fe/d as ferrous fumarate for 6 months (n 80) and was compared with a matched static cross-sectional control group (CG) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…These findings echo those obtained from a recent meta-analysis of 18 randomized controlled trials (including 5468 children aged 6 months to 5 years), which showed that children who consume micronutrient-fortified milk and cereal-based products have improved hemoglobin (Hb) levels (an increase of 0.87 g/dL) and a 57% lower risk of anemia compared with children who consume similar non-fortified items [18]. These findings are consistent with those obtained from other datasets around the world, including the NHANES study [19] and other randomized controlled trials [20,21] as well as those performed in developing countries such as India [22,23], Bangladesh [24], the Ivory Coast [25], Cameroon, and Vietnam [26]. Taken together, these studies suggest that fortified infant cereals are a potential source of iron for this subgroup of children in developed and developing countries.…”
Section: Introductionsupporting
confidence: 79%
“…These findings echo those obtained from a recent meta-analysis of 18 randomized controlled trials (including 5468 children aged 6 months to 5 years), which showed that children who consume micronutrient-fortified milk and cereal-based products have improved hemoglobin (Hb) levels (an increase of 0.87 g/dL) and a 57% lower risk of anemia compared with children who consume similar non-fortified items [18]. These findings are consistent with those obtained from other datasets around the world, including the NHANES study [19] and other randomized controlled trials [20,21] as well as those performed in developing countries such as India [22,23], Bangladesh [24], the Ivory Coast [25], Cameroon, and Vietnam [26]. Taken together, these studies suggest that fortified infant cereals are a potential source of iron for this subgroup of children in developed and developing countries.…”
Section: Introductionsupporting
confidence: 79%
“…In addition, a recent study in children aged 6-12 months in India using a similar but rice-based IC (providing 3.75 mg iron/day as ferrous fumarate) fed for 6 months showed better iron status and reduced risk for anemia and iron deficiency in association with more favorable neurodevelopmental scores (Awasthi et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Fortifying food with micronutrients has been identified as an intervention option (along with supplementation and increased dietary diversity) to tackle malnutrition, particularly in situations requiring rapid results (Binns et al 2020;Timotijevic et al, 2013). In regions where rice is a dietary staple, rice-based fortified cereal is a cost-effective option to reduce micronutrient deficiencies and anemia by providing additional dietary iron (Awasthi et al, 2020;Fiorentino et al, 2018). An efficacy study by Awasthi et al (2020) found that rice-based cereal fortified with a low to moderate dose of iron was safe for infant consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In regions where rice is a dietary staple, rice-based fortified cereal is a cost-effective option to reduce micronutrient deficiencies and anemia by providing additional dietary iron (Awasthi et al, 2020;Fiorentino et al, 2018). An efficacy study by Awasthi et al (2020) found that rice-based cereal fortified with a low to moderate dose of iron was safe for infant consumption. Children who consumed the fortified cereal also had better bloodiron status and development in language, motor skills, and socio-emotional and adaptive behaviors when compared to children who did not consume it.…”
Section: Discussionmentioning
confidence: 99%